Raw Material Usage and Process Order Module Development using SAP: A Case Study from General Packaging Manufacturer - Richard, Richard; Setiawan, Julius Raymond; Surya, Mahenda Metta (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2020)
ERP systems widely used in manufacturing companies, as manufacturing order and costing become a key component in the core business process. In order to increase the management effectiveness in the company, raw material usage in the manufacturing process becomes essential data to be discovered by the company, as the production cost derived from the usage of the raw material itself. SAP ERP can be customized and tailored to meets the business process needs as the leading software company in providing end-to-end ERP Systems. This research uses the UML diagram in the module design process, and the module application itself built under the SAP environment. With the outcome of ERP system module design from this research, the company could discover manufacturing process efficiencies by utilizing a set of system modules.